2020
DOI: 10.1590/0037-8682-0504-2020
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of concomitant infections in the coronavirus disease 2019 pandemic era: Severe acute respiratory syndrome coronavirus 2 infection in a patient with chronic Chagas disease and dimorphic leprosy

Abstract: Coronavirus disease 2019 (COVID-19) was first officially described in Brazil on February 26 th , 2020. The accumulation of reports of concomitant infections with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and pathogens that cause diseases endemic to tropical countries, such as dengue and chikungunya fever, has started to draw attention. Chagas disease and leprosy remain public health problems in many developing countries, such as Brazil. In this manuscript, we describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
4
0
3
Order By: Relevance
“…[4] Leprosy patients represent a vulnerable population that needs attention. [30,31] Although the intended sample size was achieved, and the final model showed a clinically relevant result, some limitations must be acknowledged. The existence of confounders must always be considered in observational protocols, although prospective studies are paramount for adequate clinical trial design.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Leprosy patients represent a vulnerable population that needs attention. [30,31] Although the intended sample size was achieved, and the final model showed a clinically relevant result, some limitations must be acknowledged. The existence of confounders must always be considered in observational protocols, although prospective studies are paramount for adequate clinical trial design.…”
Section: Discussionmentioning
confidence: 99%
“…Alberca et al reported fatal cases of elderly Brazilian patients coinfected with CD and COVID-19 [13]. The case of a Brazilian woman with concomitant leprosy, CD, and cutaneous/mucosal manifestations of the coronavirus infection has been reported and the authors speculate that, although the patient had borderline leprosy and CCC, she did not show any recrudescence of leprosy symptoms, worsening of cardiac symptoms, or severe COVID-19, a fact possibly explained by immunomodulatory properties of the leprosy treatment she had previously undergone [14]. Although CD cases in the Brazilian Southeast region comprise less than 5% of the total prevalence in Brazil, COVID-19-CD cases may be an important cause of uninvestigated death in endemic regions.…”
Section: Covid-19 and Protozoan Infectionsmentioning
confidence: 99%
“…Then, two other fatal cases were reported in cardiac transplant patients because of CD myocardiopathy; the two of them died due to respiratory insufficiency caused by COVID-19 and CMV reactivation (29). Finally, another case reports a Brazilian woman with COVID-19 who survived; she had Chagas cardiomyopathy (congestive cardiac failure and arrhythmia right bundle branch block treated with a pacemaker, propranolol, and an anticoagulant) and dimorphic leprosy (30). The scarce information about this coinfection, after more than 18 months of the COVID-19 pandemic, shows again that CD is a neglected disease, as there is almost no information for this population.…”
Section: Discussionmentioning
confidence: 99%